Determinasi Variabel Makro dan Mikro Ekonomi terhadap Penawaran Beras di Kabupaten Aceh Barat - Syahril, Syahril; Zibran, Zibran (universitas teuku umar, 2025)
This study aims to analyze the influence of population size, rice prices, and diesel fuel prices on rice supply in West Aceh Regency. A quantitative approach was used in this research, utilizing time series data over a ten-year period, from 2012 to 2021. The data was analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, population size, rice prices, and diesel prices do not have a significant effect on rice supply in West Aceh Regency. Although these three variables are not statistically significant, it is possible that the theories remain valid, but local-specific conditions or structural constraints may be obstructing a rational market response.Keywords: rice supply, population size, rice prices, diesel prices.